The Imperative of Skills Development for the Structural Transformation of Sub-Saharan Africa : Potential for China-World Bank-Africa Collaboration - Bashir, Sajitha (World Bank, Washington, DC, 2015)
This paper proposes three ways in which China and the World Bank could collaborate in the area of skills development in Africa, building on the experience of both and recent efforts at collaboration. First, under the PASET initiative, China and the World Bank could undertake joint analytical work to assess the skills needs for different sectors in individual countries, continue the benchmarking of African universities piloted with Shanghai Jiao Tong University, share the development experience of China through targeted learning visits, and share experiences in skills development through regional forums. Second, China could support the regional initiatives of the PASET such as the establishment of the Regional Scholarship Fund for postgraduate studies in applied sciences, engineering and technology; the proposed regional TVET centres of excellence; and co-financing of the regional Africa Centres of Excellence project, currently financed by the World Bank. This would supplement China’s on-going investments, which could also benefit from the experience of well-designed programs with strong monitoring and evaluation. Third, China could co-finance country-level projects which are being prepared with World Bank assistance, focusing on technical/vocational and higher education. This will enable Chinese Ministries and institutions to learn from the experience of the World Bank and contribute to the development of the education and training system in Sub-Saharan African countries, while also contributing China’s experience in a concrete fashion.